Synthesis and characterisation of the new oxyselenide Bi2YO4Cu2Se2. - Evans, J; Brogden, E; Thompson, A; Cordiner, R (2002)
In this communication we report the synthesis, structure and preliminary characterisation of Bi2LnO4Cu2Se2 (Ln = Y, Gd, Sm, Nd, La) phases; these materials are members of a new family of layered oxychalcogenides.